Ki legyen az aláíró? : vita a minisztertanácsban a trianoni békediktátum aláíróinak személyéről - Vizi, László Tamás (Közép-Európai Közlemények, 2010)
The representative of the Hungarian peace delegation took over the final regulations of the peace conference that closed the I. World War, in the beginning of May 1920. The peace treaty dislocated Hungary and with the disannexed territories millions of Hungarians were forced to live in the neighbouring countries. The Hungarian government could react for this dramatic and significant event in two ways: on one hand accept and undersign, on the other side refuse its signatory. After a long debate, the government and the assembly –notwithstanding the public‟s dismissal –were under the necessity of the pressure of the victorious powers, and made up their mind of signature. This study leads on this decisionmaking progress, on the strength of the elaboration and analysis of the reports of the government meetings in May 1920. The first part of the study shows debates in the meetings of the cabinet council and the political circumstances of the decision. The second part, in turn, shows the dramatic progress of the decisionmaking, as a result of which they pointed the representatives, whose task was the signature on the 4th June 1920 in the Castle of Grand Trianon. As a part of this, the study examines the personal decisions, the possible signatories, the ones who previously undertook the task. The study furnishes an answer for the controversial question, that why Dr. Ágost Benárd, welfare and labour minister and Alfréd Drasche-Lázár, extraordinary delegate were chosen by the government for the signature.